2021
DOI: 10.3389/fbioe.2021.766599
|View full text |Cite
|
Sign up to set email alerts
|

Shape Optimization of Costal Cartilage Framework Fabrication Based on Finite Element Analysis for Reducing Incidence of Auricular Reconstruction Complications

Abstract: Skin necrosis is the most common complication in total auricular reconstruction, which is mainly induced by vascular compromise and local stress concentration of the overlying skin. Previous studies generally emphasized the increase in the skin flap blood supply, while few reports considered the mechanical factors. However, skin injury is inevitable due to uneasily altered loads generated by the intraoperative continuous negative suction and uneven cartilage framework structure. Herein, this study aims to atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…FEA is a highly versatile tool for simulating material behavior under diverse loads. [ 65 ] Several studies have demonstrated the effectiveness of compression therapy in reducing scars. To ensure optimal treatment outcomes, it is recommended to maintain a pressure range between 15 and 40 mmHg.…”
Section: Resultsmentioning
confidence: 99%
“…FEA is a highly versatile tool for simulating material behavior under diverse loads. [ 65 ] Several studies have demonstrated the effectiveness of compression therapy in reducing scars. To ensure optimal treatment outcomes, it is recommended to maintain a pressure range between 15 and 40 mmHg.…”
Section: Resultsmentioning
confidence: 99%
“…Radioss software (HyperWorks 14.0, Altair, USA) was used to simulate the compressive progress. 64 A time-displacement load was added to the top plane to simulate the compressive process, while a fixed constraint was added to the bottom plane. The material properties applicable to the description of the viscoelastic materials in the Radioss software, MAT/LAW69 and MAT/LAW70, were imported into the PUA composite resin specimens for calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Chiesa et al 105 conducted a rheological characterization of a newly developed self-assembling peptide hydrogel, simulated the printing of wood-pile scaffolds, predicted the biomechanical properties of self-assembling peptide hydrogel using FE models, and ultimately successfully 3D bioprinted human ear-shaped scaffolds with in vivo dimensions and several protrusion planes, saving both time and materials. Zhong et al 106 were the first to use FEA to simulate Nagata’s one-stage modified-surgical procedure and used FEA to optimize the surgery and ear framework design. Clinical application and follow-up revealed that, compared with the one-stage Nagata-modified surgery, the optimized method significantly reduced the incidence of postoperative skin necrosis and cartilage exposure.…”
Section: Digital-assistive Technologymentioning
confidence: 99%